Pengaruh Motivasi Berwirausaha, Kemandirian Dan Efikasi Diri (Self Efficacy) Terhadap Keberhasilan Usaha Pada Penyandang Disabilitas Di Kota Malang - Reza Alvinova Amalia Dewi; Muhammad Agus Salim; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The rapid development of MSMEs is a manifestation of true entrepreneurship and is deeply rooted in the daily work of entrepreneurs in their respective fields of business. Like ordinary people, people with disabilities need decent work to continue living with all the limitations despite all the limitations they have. The purpose of this study is to determine and analyze the variables of entrepreneurship motivation, independence and self-efficacy that affect business success in people with disabilities in the city of Malang by applying snowball sampling technique with several criteria obtained as many as 60 respondents. The research method uses multiple linear regression tests such as t test, R square determination and F test to obtain the results that simultaneously the variables of entrepreneurial motivation, independence, and self-efficacy affect business success, while partially self-efficacy does not affect business success. Keywords : Entrepreneurial Motivation, Independence, Self-Efficacy, Business Success